If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x+5+4x=-(3x+4)+2
We move all terms to the left:
-2x+5+4x-(-(3x+4)+2)=0
We add all the numbers together, and all the variables
2x-(-(3x+4)+2)+5=0
We calculate terms in parentheses: -(-(3x+4)+2), so:We get rid of parentheses
-(3x+4)+2
We get rid of parentheses
-3x-4+2
We add all the numbers together, and all the variables
-3x-2
Back to the equation:
-(-3x-2)
2x+3x+2+5=0
We add all the numbers together, and all the variables
5x+7=0
We move all terms containing x to the left, all other terms to the right
5x=-7
x=-7/5
x=-1+2/5
| -3(4x-7)=5x+6 | | 3+4n=5n+6 | | 1+4(5x+2)=6x+23 | | 12.5=5x-3.75 | | 3/2(x-5)=2x+10 | | 5.1=-7.4+5w | | 4/5w=16.08 | | 2/3=2m=5=4 | | -7x+6x+4=-6x+6x-3 | | 10c–6=10c+7 | | (t-3)/2=75 | | -2-4/5x=13 | | 28=1/2•7h | | 10(x-1)=4 | | 700–35w=450+15w | | X+9÷2=3x | | x^2=6(x-3) | | 2(x-6)=32 | | 2(x+6)=-2(x+4) | | n/4-21=-3 | | a=5+-5a+5 | | y/15.36+5=11 | | -12=n/2=6 | | 4/5w=164/5 | | 130+45x=70+45x | | 4/5=24/(x+5) | | 90x-60=120 | | 4x^2-59x+207=0 | | 3(c-6)=78/3 | | -1.75=p+4.85 | | x-34=-40 | | 2w(w+1)(w-5)=0 |